Administrative justice in times of crisis: a commitment to arbitration - García Pérez, Marta (Universidad Nacional del Litoral, 2014)
This paper analyzes the situation of administrative justice in Spain, from the information published by Consejo General del Poder Judicial. It is proposed to search for ways that will reduce litigiousness or, when this goal is not achieved, the regulation of extrajudicial remedies, such as arbitration.